Development Of An Integrated Financial Management System For Rw 09 Waste Bank – Pojok 3r Jatisari Education Park To Improve Financial Performance - Septian Fajar Hidayat; Misbahuddin Misbahuddin; Afna Mutia Salsabila; Asep Jamaludin; Gusneli Gusneli (Jurnal Multidisiplin Indonesia, 2026)
Background: Accurate financial management is an essential factor in ensuring the sustainability of waste bank operations. The Waste Bank of RW 09 – Pojok 3R Jatisari Education Park still relies on manual recording methods, which potentially lead to data errors, reporting delays, and difficulties in monitoring customer balances and waste volumes in real-time. This community service program aimed to develop an integrated financial management system based on Microsoft Excel to enhance transparency, efficiency, and accountability in waste bank financial operations. The implementation method employed a participatory approach encompassing five stages: field observation and needs analysis through interviews with administrators; system design incorporating daily transaction inputs, automatic balance recaps, cash reports, and visual dashboards; internal development and testing through transaction simulations; training and implementation with direct mentoring for two weeks; and evaluation through satisfaction questionnaires, observations, and interviews. Five waste bank administrators participated in the program. The developed system successfully automated transaction recording, customer data management, financial report generation, and provided visual dashboards for monitoring savings growth and waste volume. Post-implementation evaluation revealed significant improvements: recording efficiency increased from 20 minutes to 5 minutes per transaction; recording errors decreased from 8-10% to less than 1% per month; and all administrators demonstrated ability to operate the system independently. Administrators reported enhanced administrative governance and increased community participation in recycling activities.